Morphological, chemical surface and filtration characterization of a new silicon carbide membrane. Issue 3 (March 2017) - Fraga, M.C.; Sanches, S.; Pereira, V.J.; Crespo, J.G.; Yuan, L.; Marcher, J.; de Yuso, MªV. Martínez; Rodríguez-Castellón, E.; Benavente, J.
Abstract: A new silicon carbide ceramic membrane consisting of a unique top layer on a SiC support for application in oily wastewaters filtration was produced and characterized in terms of morphology and chemical surface composition by scanning electron microscopy and X-ray photoelectron spectroscopy measurements. The manufacturing process of this new membrane allows time and economic savings when compared with a two layers membrane previously obtained. The new membrane has a smooth top layer with controlled porosity and a higher permeability compared to already developed commercial membranes. Moreover, it is extremely efficient to remove total suspended solids as well as oil and grease and, consequently, it can be applied to effective treatment of industrial oily wastewaters.